Preliminary report on the comparative weed suppressibility of Bangladeshi Wheat varieties - Islam, A. K. M. Mominul; Uddin, Md. Nasir; Yeasmin, Sabina; Kheya, Sinthia Afsana; Islam, Md. Shafiqul; Ahmed, Sharif; Hossain, Akbar; Anwar, Md. Parvez (Elsevier, 2023)
A key and ecologically sound strategy for integrated weed management is the use of varieties of weed-competitive crops. Utilizing wheat cultivars that are weed-competitive can lessen weed pressure and inordinate herbicide usage in wheat fields by a substantial amount. To assess the weed suppressibility of Bangladeshi wheat varieties, a field test was carried out in 2018 throughout the winter season at the Agronomy Field Laboratory, Bangladesh Agricultural University, Bangladesh. Tests on a total of 18 selected Bangladeshi wheat cultivars were conducted in both "weedy" and "weed-free" environments. Additionally, weed monoculture plots (without wheat) were kept. The experiment was replicated three times using a randomized complete block design (RCBD). The results demonstrated that wheat varieties' weed interference and production capabilities differed greatly. BARI Gom 22 permitted the most weed growth (35 m-2), whereas BARI Gom 23 allowed the least (15 m-2) at 60 DAS among the wheat types under study. Grain yield ranged between 4.42 t ha-1 (BARI Gom 20) and 5.45 t ha-1 (BARI Gom 26) in weed-free settings, whereas it fluctuated from 2.48 t ha-1 (BARI Gom 21) to 3.93 t ha-1(BARI Gom 33) in weedy condition. The extent of the relative yield loss brought on by weeds ranged from 24 to 53%, with BARI Gom 33 suffering the least and Binagom-1 suffering the most. The weed competitive index varied from 0.48 to 1.47 for the examined wheat types. Among the cultivars, Binagom-1 had the lowest WCI and BARI Gom 29 had the highest. Although BARI Gom 33 was the best yielder in weedy condition and had the lowest relative yield loss, its interference against weed was moderate. Relative to the other varieties under consideration, comparatively BARI Gom 33 was the best in terms of yield and weed interference, but it is also advocated that breeders should continually focus on developing a variety that has both excellent producing potential and robust weed suppression